Distorção da autopercepção de imagem corporal em adolescentes - Nogueira-de-Almeida, Carlos Alberto (2022)
Introduction: During adolescence, a period of acceleration of growth and body changes, there may be contending behaviors that make the individual vulnerable to concerns about his or her body and appearance. Objective: To verify the presence of body image self-perception distortion in adolescents of the city of Ribeirão Preto, SP. Methods: The present work is a cross-sectional, observational and analytical study. A total of 343 adolescents aged between 12 and 19 years old and belonging to the Professional Information Program (PIP, in the Portuguese acronym) of the University of Ribeirão Preto, state of São Paulo, Brazil, were evaluated. The adolescents responded how they considered themselves in relation to their body weight. Anthropometric measurements of the participants (weight, height, and body mass index [BMI]) were performed. The presence of body image distortion was assessed through the discrepancy between the BMI diagnosed by the professional and the BMI perceived by the adolescent. Results: There was a prevalence of 41.7% of adolescents with body image distortion, either due to overestimation or underestimation of the body size. Female adolescents had greater distortions in the perception of self-image. The overestimation of body image was higher in eutrophic adolescents, while the underestimation was greater in obese and overweight adolescents. Conclusion: The results indicate the need to implement public policies and projects within the school context for the prevention of body image and eating disorders, including in eutrophic adolescents.